2014
DOI: 10.1308/003588414x13814021678952
|View full text |Cite
|
Sign up to set email alerts
|

The misleading appearance of silver nitrate on plain radiography

Abstract: Cauterisation with silver nitrate is commonly used to treat overgranulation. Silver nitrate has a high density and a high mass attenuation coefficient, and it is therefore highly radio-opaque. We present a case in which its topical application to an area of overgranulation was interpreted as a bony fragment by the reporting radiologist in a patient with a supracondylar humeral fracture whose radiograph after removal of K-wires showed a large radio-opaque lesion. Although not a new phenomenon, it is one not wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…As a metal its mass attenuation coefficient is described as high as 14 times that of cortical bone. 3 This explains why only a thin layer over granulation tissues is mistaken for bone within the EAC as it is a narrow canal surrounded by bone. Further doubt is created in the context of NOE due to surrounding soft tissue swelling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a metal its mass attenuation coefficient is described as high as 14 times that of cortical bone. 3 This explains why only a thin layer over granulation tissues is mistaken for bone within the EAC as it is a narrow canal surrounded by bone. Further doubt is created in the context of NOE due to surrounding soft tissue swelling.…”
Section: Discussionmentioning
confidence: 99%
“…8 Further literature review highlighted a case in which wrongfully, a bony fragment in a supracondylar humeral fracture was reported on plain radiographs in the absence of clinical correlation. 3 Healy et al reported two cases in which silver nitrate was incorrectly identified as a foreign body on plain radiographs of the fingers. 9 A similar case was described by Peter Vu et al, in which the patient unfortunately underwent surgical intervention due to the artefactual appearance of fingertip heterotopic ossification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Because of these antiseptic and wound healing properties, it is commonly used as a topical agent for cauterising bleeding points; especially over mucosal surfaces, burning granulations and even cauterising the non-healing ulcers for acceleration of the healing process. 3 Granulations in necrotizing otitis externa (OE) are very common and are considered to be one of the diagnostic criteria. 4 These lesions are often managed by applying silver nitrate especially after taking biopsies due to its dual effect.…”
mentioning
confidence: 99%